KEARIFAN RITUAL DAN SOSIAL SYAIR-SYAIR SUFI - Kholil, Ahmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
Substantially, â€œTasawufâ€ as the way towards God had been existing since the prophet age; but it was just at the end of the second Hijriyah this term that was known as zuhud became then popularly known as tasawuf. After Islam develops, marked by variety of traditions and sciences as the result of the contribution of various culture expressed through knowledge, tasawuf becomes clear in Islam. Some intellectuals donâ€™t see tasawuf as pure Islam, because some teachings related to certain rituals reflect some tradition and culture. Many intellectuals agreed to Nasrâ€™s opinion, and there are many western intellectuals know tasawuf (Sufism) better than Islam. Now tasawuf has been considered by many people as a universal spiritual value and it is as eternal as Islam. Syawqi Doif, an Arabic intellectual who wrote a lot about the history of Arabic culture and literature, in his book entitled al-Tarikh al-Adab fi al-Ashr al-Abbasyi al-Tsani, especially about zuhud and tasawuf. This paper discussed about tasawuf followed by poems written by mutashawwifin discussing about sufiâ€™s terms. Many sufis left behind them literary works which describe the way they believe. The writer quoted and discussed some poems based on his understanding.Keywords